Discrepancies of video head impulse test results in patients with idiopathic sudden sensorineural hearing loss with vertigo and vestibular neuritis - Liu, Yingzhao; Leng, Yangming; Zhou, Renhong; Liu, Jingjing; Wang, Hongchang; Xia, Kaijun; Liu, Bo; Xiao, Hongjun (Frontiers in Neuroscience, 2023)
Objective Sudden sensorineural hearing loss with vertigo (SHLV) and vestibular neuritis (VN) remain frequent causes of acute vestibular syndrome (AVS). The aim of study was to compare the results of video head impulse test (vHIT) in patients with SHLV and VN. The characteristics of high-frequency vestibule-ocular reflex (VOR) and the differences of the pathophysiological mechanisms underlying these two AVS were explored. Methods Fifty-seven SHLV patients and 31 VN patients were enrolled. vHIT was conducted at the initial presentation. The VOR gains and occurrence of corrective saccades (CSs) of anterior, horizontal, and posterior semicircular canals (SCCs) in two groups were analyzed. Pathological vHIT results refer to impaired VOR gains and presence of CSs. Results In SHLV group, pathological vHIT results was most prevalent in the posterior SCC on the affected side (30/57, 52.63%), followed by horizontal (12/57, 21.05%) and anterior SCC (3/57, 5.26%). In VN group, pathological vHIT preferentially affected horizontal SCC (24/31, 77.42%), followed by anterior (10/31, 32.26%) and posterior SCC (9/31, 29.03%) on the affected side. As for anterior and horizontal SCC on the affected side, the incidences of pathological vHIT results in VN group were significantly higher than those in SHLV group (β = 2.905, p < 0.01; β = 2.183, p < 0.001). There were no significant differences in the incidence of pathological vHIT result in posterior SCC between two groups. Conclusion Comparison of vHIT results in patients with SHLV and VN revealed discrepancies in the pattern of SCCs impairments, which may be explained by different pathophysiological mechanisms underlying these two vestibular disorders presenting as AVS.